Neighboring houses: Report from an archaeological trench at Store Sandvika, Hasvik, Finnmark - Jørgensen, Erlend Kirkeng (Septentrio Reports, 2022)
In august of 2018, a minor excavation was made across two adjoining Stone Age house pit features at the newly discovered site of Store Sandvika (Site ID: 221255, Hasvik municipality, Finnmark county), as part of the Stone Age Demographics project at UiT The Arctic University of Norway. The objectives mainly concerned: To look for stratigraphically identifiable features useful for the understanding of house contemporaneity and the identification of multiple occupation phases. To look for the preservation of organics, such as bone/wood tools or organic refuse. To identify datable material from multiple horizons within each house. Shoreline displacement suggests that the terrace was suitable for habitation already at the earliest post-glacial colonization, and that the isostatic uplift made the lower laying terrace of 12-10 masl inhabitable by approx. 10.000 years ago (cal BP). However, the transgression of the entire lower terrace would make the upper terrace into the only inhabitable surface in the Store Sandvika bay for millennia. This now also appears to be confirmed by the dates produced from the site. Datable material was only retrievable from one of the houses, all centering on 3600 BC. The lack of datable material from the other house made it difficult to determine questions of contemporaneity and temporal relatedness, yet stratigraphic evidence suggest variable age and possible reuse of the houses given the stark variation in peat thickness covering the adjoining houses, as well as the apparent secondary dug-down in one of the houses. Repeated reuse of the site seems likely based on both the identification of debitage from chert/silicified slate below the house floor of what stratigraphically speaking should be the oldest house – as well as dates most likely indicating tightly spaced, yet separate habitation events. No artifacts or debitage whatsoever was uncovered within the house areas. The dates should imply that the houses most likely would contain rich slate tool inventories as is common for house features of this period. The lack of finds may solely be credited to the very minimal spatial extent of the investigation – however specific waste management practices favored by the steep and ocean-front terrace, may also contribute to less within house debitage. The report ends with a contextualization of the site focusing on the specificity of Younger Stone Age sites located atop fluvial deltas elevated significantly above contemporaneous sea level and factors that might affect the data catchment and inventories from such sites – such as waste management practices.